Misinformation, social status and ridicule: A study of how Danes spread and react to Covid-19 misinformation on Twitter - Kjær, Cathrine Valentin; Johansen, Nicklas; Marjanovic, Sara Vera; Baglini, Rebekah; Adler-Nissen, Rebecca (Politica, 2022)
How do Danes interact with misinformation on social media? Which statements and arguments do they use to spread and reject misinformation? We investigate digital misinformation during the Covid-19 pandemic and analyze how citizens spread and reject information about facemasks on Twitter in Denmark. Our study shows that the amount of misinformation is limited, but that false claims are not predominantly countered through fact-checking or dialogue. Instead, users who reject the misinformation often use irony and condescending comments to distance themselves from those who spread misinformation and whose concerns are thus not taken seriously. Our findings question citizens’ ability to effectively correct misinformation online and point to the importance of group affiliation and social status not only in spreading, but also in rejecting digital misinformation. Keywords: Covid-19, humor, misinformation, social status, Twitter